Association of the Biopsychosocial Factors Adverse Childhood Experiences, Adult Attachment Style, Emotion Regulation, and Mitochondrial Density in Immune Cells with Major Depressive Disorder - Katharina Strecker; Eun-Jin Sim; Kathrin Woike; Carlos Schönfeldt-Lecuona; Peter Radermacher; Alexander Karabatsiakis; Markus Kiefer (Neuroimmunomodulation)
Introduction: Major depressive disorder (MDD) is one of the most prevalent mental disorders associated with various negative impacts such as lower overall quality of life, increased morbidity risk, and even premature mortality. According to the biopsychosocial model of health and disease, multiple factors contribute to the development and manifestation of MDD. Here, we assessed preselected social, psychological, and biological variables and tested their power to predict MDD diagnosis using logistic regression models. Methods: In 24 patients with current MDD diagnosis and 35 healthy control participants, the following variables were measured to test for associations with MDD diagnosis: (1) emotional neglect and adult attachment style as social variables, (2) thought suppression and cognitive reappraisal as psychological variables, and (3) mitochondrial density (citrate synthase activity as a surrogate marker of mitochondrial density) measured in peripheral blood mononuclear cells (PBMCs) as a biological variable. Results: The following biopsychosocial variables were associated with MDD diagnosis. Participants with greater emotional neglect (OR: 1.273, 95% CI: 1.059–1.645), higher levels of intrusive thoughts (OR: 1.738, 95% CI: 1.282–3.066), and decreased mitochondrial density in PBMCs (OR: 0.298, 95% CI: 0.083–0.784) had a higher probability of belonging to the MDD group. Conclusions: In line with biopsychosocial models of depression, the present results indicate that variables at different levels of analysis are conjointly related to MDD. These findings open new perspectives for the diagnosis and treatment of MDD, but they need to be replicated in larger samples in the future.